171 Resurgery in Craniovertebral Junction Abnormalities. (August 2016) - Sindgikar, Pavaman Pandit; Das, Kuntal Kanti; Jaiswal, Awadesh K.; Sahu, Rabi Narayan; Srivastava, Arun K.; Mehrotra, Anant; Sardhara, Jayesh Chunilal; Bhaisora, Kamlesh Singh; Behari, Sanjay
Abstract : INTRODUCTION: Surgery for craniovertebral junction (CVJ) abnormalities like atlantoaxial dislocation (AAD) with or without basilar invagination (BI) and/or with or without associated Arnold-Chiari malformation (ACM) cause high cervical myelopathy. Occasionally, mechanical factors such as inadequate canal decompression, torticollis, and/or scoliosis may lead to lack of improvement following the primary surgery. Also, implant-related factors requiring its revision/removal or surgical site infections may cause patient to undergo resurgery. This study was aimed at highlighting the underlying etiopathogenesis of resurgery(ies) following primary surgery in CVJ abnormalities. METHODS: Data of 55 patients undergoing resurgery included clinicoradiological assessment and operative records. Inclusion criteria included failed primary procedure, redo procedure for construct failure, infection at the surgical site, or wound dehiscence. Pure ACM patients without bony anomalies were excluded from the study. RESULTS: One hundred thirty-seven procedures were performed in 55 patients. Causes of resurgery could be divided into ventral (redo or de novo transoral decompression [TOD]/wound complications, n = 33, 40.2%) and dorsal causes (implant-related factors/wound infections, n = 49, 59.8%). De novo TOD was done in persisting myelopathy following posterior fusion (PF) with distraction (n = 15, 18.3%). Redo TOD was done for residual anterior bony compression (n = 8, 9.6%, odds ratio 0.61 [confidence interval 0.20-1.86]). Causes for oral wound reexplorations (n = 10, 12.2%) included velopharyngeal insufficiency, wound resuturing, oral bleeding, and cerebrospinal fluid (CSF) leak. Dorsal causes included: (1) Implant factors (n = 27, 32.7%) and (2) neck wound reexplorations (n = 22, 26.8%). Presence of subaxial spine scoliosis, torticollis, and asymmetric joints increased the incidence of reexploration. Occipitocervical fusion rather than C1-2 fusion was more prone toward construct loosening. CONCLUSION: Patients undergoing distraction with posterior fusion required transoral surgery because of factors described earlier. Single-stage TOD+PF increases the chance of implant infection due to tissue contamination, bacteremia, and transfacetal migration of microbes. Chronic/recurrent sinus is usually suggestive of deeper infection and can be cured with implant removal.